2007
DOI: 10.1017/s0007114507756933
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D3 affects vitamin D status similar to vitamin D3 in pigs – but the meat produced has a lower content of vitamin D

Abstract: In food databases, the specific contents of vitamin D 3 and 25-hydroxyvitamin D 3 in food have been implemented in the last 10 years. No consensus has yet been established on the relative activity between the components. Therefore, the objective of the present study was to assess the relative activity of 25-hydroxyvitamin D 3 compared to vitamin D 3 . The design was a parallel study in pigs (n 24), which from an age of 12 weeks until slaughter 11 weeks later were fed approximately 55 mg vitamin D/d, as vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 24 publications
5
78
3
1
Order By: Relevance
“…Moreover, we have found a significant negative association between 25-OH D levels and total body lean mass. It has been reported in animal studies, that 25-OH D stores are distributed in the body fat and also in muscle tissue (Jakobsen et al, 2007). Therefore, it is tempting to speculate that muscle can create another reservoir of vitamin D also in humans.…”
Section: Hypovitaminosis D and Body Composition Indicesmentioning
confidence: 96%
“…Moreover, we have found a significant negative association between 25-OH D levels and total body lean mass. It has been reported in animal studies, that 25-OH D stores are distributed in the body fat and also in muscle tissue (Jakobsen et al, 2007). Therefore, it is tempting to speculate that muscle can create another reservoir of vitamin D also in humans.…”
Section: Hypovitaminosis D and Body Composition Indicesmentioning
confidence: 96%
“…The amounts of vitD3 and 25OHD3 in fish were detected and quantified by use of HPLC-UV/PDA [18,19] or liquid chromatography combined with triple quadrupole mass spectrometry and electrospray ionisation (LC-MS/MS-ESI) [20]. The equipment used being HPLC-UV/PDA from Waters (Alliance 2695; UV-detector 2487; PDA-detector 2996, Milford, MA) and LC-MS/MS from Agilent (LC 1200 and MS 6460, Agilent Technologies, Santa Clara, CA).…”
Section: Fish Samplesmentioning
confidence: 99%
“…Formation of intractable emulation layer in this step was considered as a common problem in this step; Katherine M. Phillips et al, concluded that substitution of hexane with a more polar solvent such as ethyl ether and petroleum ether, detained emulsion formation using the wide range of food matrices. Regarding the type of solvents used in the extraction step, more studies could be addressed that accomplished vitamin D 3 measurement using the same solvent combination used in the present study (9,(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%